Use of lasers in hidradenitis suppurativa treatment – case report - Kozinska, Urszula; Gras-Ozimek, Jordi; Kozińska, Iga (Journal of Education, Health and Sport, 2022)
Acne inverse sometimes known as hidradenitis suppurativa is a long-term dermatological condition. Due to the poorly examined nature of the disease the effectiveness of its treatments is unclear. More than 50 interventions have been described and therefore its diagnostic and the treatment can be challenging. The aim of this case report is to draw attention to the possible use of laser therapy in the treatment of hidradenitis suppurativa. A case report. We report the case of 27-year-old woman that has been successfully treated with laser after years of an ineffective treatment. Due to the failure of systemic and local antibiotic therapy, hormone therapy, surgical drainage and orally and externally applied retinoids, removal of lesions using a CO2 laser knife and a fractional laser therapy combining a CO2 laser and a 1570 nm wavelength laser on the surface of the affected skin was performed. Conclusions. The use of laser therapy, with particular emphasis on the CO2 laser, may be an important and effective element of hidradenitis suppurativa treatment.